INVITED REVIEW‐APPLICATIONS FOR 3D PRINTERS IN VETERINARY MEDICINE. Issue 4 (29th May 2014) - Hespel, Adrien‐Maxence; Wilhite, Ray; Hudson, Judith
<x xml:space="preserve">Abstract</x> Recent technological advances in 3D printing have resulted in increased use of this technology in human medicine, and decreasing cost is making it more affordable for veterinary use. Rapid prototyping is at its early stage in veterinary medicine but clinical, educational, and experimental possibilities exist. Techniques and applications, both current and future, are explored and illustrated in this article.